Correction: Highly efficient fullerene/perovskite planar heterojunction solar cells via cathode modification with an amino-functionalized polymer interlayer. Issue 13 (14th March 2017) - Xue, Qifan; Hu, Zhicheng; Liu, Jiang; Lin, Jiahui; Sun, Chen; Chen, Ziming; Duan, Chunhui; Wang, Jing; Liao, Cheng; Lau, Woon Ming; Huang, Fei; Yip, Hin-Lap; et al.
Abstract : Correction for 'Highly efficient fullerene/perovskite planar heterojunction solar cells via cathode modification with an amino-functionalized polymer interlayer' by Qifan Xue et al., J. Mater. Chem. A, 2014, 2, 19598–19603.